A graded neonatal mouse model of necrotizing enterocolitis demonstrates that mild enterocolitis is sufficient to activate microglia and increase cerebral cytokine expression - Cuilee Sha; Trevor Van Brunt; Jacob Kudria; Donna Schmidt; Alisa Yurovsky; Jela Bandovic; Michael Giarrizzo; Joyce Lin; Styliani-Anna Tsirka; Agnieszka B. Bialkowska; Lonnie P. Wollmuth; Esther M. Speer; et al. (PLoS ONE, 2025)
Necrotizing enterocolitis (NEC) is an inflammatory gastrointestinal process that afflicts approximately 10% of preterm infants born in the United States each year, with a mortality rate of 30%. NEC severity is graded using Bell’s classification system, from stage I mild NEC to stage III severe NEC. Over half of NEC survivors present with neurodevelopmental impairment during adolescence, a long-term complication that is poorly understood. Although multiple animal models exist, none prospectively controls for NEC severity. We bridge this knowledge gap by characterizing a graded murine model of NEC and studying its relationship with neuroinflammation across a range of NEC severities. Postnatal day 3 (P3) C57BL/6 mice were fed a formula containing different concentrations (0% control, 0.25%, 1%, 2%, and 3%) of dextran sodium sulfate (DSS). P3 mice were fed every 3 hours for 72 hours. We collected data on weight gain and behavior (activity, response, body color) during feeding. At the end of feeding, we collected tissues (intestine, liver, plasma, brain) for immunohistochemistry, immunofluorescence, and cytokine and chemokine analysis. Throughout NEC induction, mice fed higher concentrations of DSS died sooner, lost weight faster, and became sick or lethargic earlier. Intestinal characteristics (dilation, color, friability) were worse in mice fed higher DSS concentrations. Histology revealed small intestinal disarray among all mice fed DSS, while higher DSS concentrations resulted in reduced small intestinal cellular proliferation and increased hepatic and systemic inflammation. In the brain, IL-2, G-CSF, and CXCL1 concentrations increased with higher DSS concentrations, and microglial branching in the hippocampus CA1 was significantly reduced in DSS-fed mice. In conclusion, we characterized a novel graded model of NEC that recapitulates the full range of NEC severities. We showed that mild NEC is sufficient to initiate neuroinflammation and microglia activation. This model will facilitate long-term studies on the neurodevelopmental effects of NEC.